Treatment of sepsis-induced acquired protein C deficiency reverses Angiotensin-converting enzyme-2 inhibition and decreases pulmonary inflammatory response - Richardson, Mark A; Gupta, Akanksha; O'Brien, Lee A; Berg, David T; Gerlitz, Bruce; Syed, Samreen; Sharma, Ganesh R; Cramer, Martin S; Heuer, Josef G; Galbreath, Elizabeth J; Grinnell, Brian W (The Journal of pharmacology and experimental therapeutics, 2008)
The protein C (PC) pathway plays an important role in vascular and immune function, and acquired deficiency during sepsis is associated with increased mortality in both animal models and in clinical studies. However, the association of acquired PC deficiency with the pathophysiology of lung injury is unclear. We hypothesized that low PC induced by sepsis would associate with increased pulmonary injury and that replacement with activated protein C (APC) would reverse the activation of pathways associated with injury. Using a cecal ligation and puncture (CLP) model of polymicrobial sepsis, we examined the role of acquired PC deficiency on acute lung injury assessed by analyzing changes in pulmonary pathology, chemokine response, inducible nitric-oxide synthase (iNOS), and the angiotensin pathway. Acquired PC deficiency was strongly associated with an increase in lung inflammation and drivers of pulmonary injury, including angiotensin (Ang) II, thymus and activation-regulated chemokine, plasminogen activator inhibitor (PAI)-1, and iNOS. In contrast, the protective factor angiotensin-converting enzyme (ACE)-2 was significantly suppressed in animals with acquired PC deficiency. The endothelial protein C receptor, required for the cytoprotective signaling of APC, was significantly increased post-CLP, suggesting a compensatory up-regulation of the signaling receptor. Treatment of septic animals with APC reduced pulmonary pathology, suppressed the macrophage inflammatory protein family chemokine response, iNOS expression, and PAI-1 activity and up-regulated ACE-2 expression with concomitant reduction in AngII peptide. These data demonstrate a clear link between acquired PC deficiency and pulmonary inflammatory response in the rat sepsis model and provide support for the concept of APC as a replacement therapy in acute lung injury associated with acquired PC deficiency.